Sintesis Surfaktan Metil Ester Sulfonat (MES) Dari Palm Oil Metyhl Ester (POME) Dan Natrium Bisulfit (NaHSO3) Dengan Variasi Waktu Sulfonasi Dan Rasio Mol Pome : NaHSO3 - Rino Hasanatul Isra; Syaiful Bahri; Wisrayetti Wisrayetti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Methyl Ester Sulfonate (MES) is an anionic surfactant which is currently being developed. These surfactants can be produced from palm oil methyl ester. MES produced from sulfonation reaction with addition of sulfonation agents. MES can be synthesized from Palm Oil Methyl Ester (POME) and Sodium Bisulfite (NaHSO3) as the sulfonation agent with Calcium Oxide as the catalyst. The aims of this research are to determine the characteristic of the product, and to determine the effects of temperature and mole ratio of the product produced. Sulfonation process was carry out at the time of 5, 7, 9 hours, the mole ratio of 1:1, 1:1,5, 1:2, the stirring speed of 450 rpm, and the temperature of 80 oC. Then purification of the MES surfactant and product analysis is carried out. The best characteristic of the MES is at time 7 hours and mole ratio 1:2 with the density of 0,943 gr/ml, the viscosity of 2,1027 cP, the pH of 3,53, the surface tension of 33,95 dyne/cm, the interfacial tension of 28,85 dyne/cm, the emulsion stability of 89%, and the yield of 83,45%. The surface tension is accordance to the commercial MES.Keyword : Methyl Ester, Methyl Ester Sulfonate, Sulfonation, Surfactant.